The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/rem.21731
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced attenuation (EA) to manage PFAS plumes in groundwater

Abstract: Remediation of per-and polyfluoroalkyl substances (PFAS) in groundwater is particularly challenging because of their unique chemical and fate and transport properties. Many conventional in-situ remediation technologies, commonly applied to address other groundwater contaminants, have proven ineffective for treatment of PFAS. Given their stability, destruction of PFAS in-situ has remained elusive as an in-situ treatment option. Consequently, new approaches to manage PFAS groundwater plumes are of great interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Surface excess can be an indicator of PFAS retention on solids and is of particular importance for modeling PFAS transport in the vadose zone where there is high air–water interfacial area. 7,35–37 We found that surface excess ( Γ max ) did not vary substantially among the conditions tested (ultrapure, ABW, ASW). An equivalent minimum surface tension was observed in all three aqueous systems (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Surface excess can be an indicator of PFAS retention on solids and is of particular importance for modeling PFAS transport in the vadose zone where there is high air–water interfacial area. 7,35–37 We found that surface excess ( Γ max ) did not vary substantially among the conditions tested (ultrapure, ABW, ASW). An equivalent minimum surface tension was observed in all three aqueous systems (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Environmental Science: Processes & Impacts interfacial area. 7,[35][36][37] We found that surface excess (G max ) did not vary substantially among the conditions tested (ultrapure, ABW, ASW). An equivalent minimum surface tension was observed in all three aqueous systems (Fig.…”
Section: Papermentioning
confidence: 72%
See 1 more Smart Citation
“…MNA was established as a groundwater remedy in the mid‐1990s through early 2000s (U.S. EPA 1999; National Research Council [NRC] 2000; Suthersan 2001). Evidence for its applicability has been expanded over time for contaminant classes including: petroleum hydrocarbons (Newell and Connor 1998; ASTM 2016), wood preservatives (Stroo et al 1997), chlorinated solvents (U.S. EPA 1998; ITRC 1999); MTBE (U.S. EPA 2005a), metals and other inorganics (U.S. EPA 2007, 2009, 2015), radionuclides (U.S. EPA 2010), perchlorate (ESTCP 2010), and 1,4‐dioxane (Adamson et al 2015). The newest frontier for evaluating the applicability of MNA as an effective groundwater remedy is undoubtedly PFAS (e.g., Newell et al 2021a, 2021b).…”
Section: What Are Natural Remedies?mentioning
confidence: 99%
“…Interactions between LNAPL (either mobile or residual) and PFAS have important implications for remedial strategies at contaminated sites. Recently, Newell et al (2022) explained how monitored natural attenuation (MNA) could be considered for PFAS sites in light of the fact that perfluoroalkyl acids such as PFOS and PFOA are unlikely to be degradable by naturally occurring microbes under relevant environmental conditions. A primary conclusion from these authors was that "retention" is a term and concept that should be considered for PFAS conceptual site models and the evaluation of PFAS natural attenuation.…”
Section: Implications For Site Characterization and Remedial Strategymentioning
confidence: 99%